Local stability analysis of a competition model of two different species in an ecosystem - Narca, Mary Joyce R.; Almocera, Lorna S. (Cebu City College of Science, University of the Philippines Cebu, 2019)
The populations of two-competing species in an ecosystem are governed by ẋ = ẋ(1 − aẋ) − ẋy; y = y(b − y) − ẋy + h where x represents the population of the first specie; y represents the population of the second specie; x represents the change of the population of the first specie over time; y represents the change of the population of second specie over time; h represents constant migration rate of one specie over time (h = 0, h > 0, h < 0) and a & b are positive constants with a as the first specie?s intraspecific competition coefficient and b as the second specie?s intrinsic rate of increase. The existence and stability of equilibrium points were proven and determined. Furthermore, numerical examples were presented to support the analytical results obtained.
Thesis (Bachelor of Science in Mathematics)--University of the Philippines Cebu. June 2019.